2022
DOI: 10.1111/jtxs.12655
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and tribological characterization of different commercial hazelnut‐based spreads

Abstract: Five commercial hazelnut/cocoa spreads with different compositions were tested by rheology/tribology. The impact of each formulation on the structural/lubricant performances was investigated. Rotational/oscillatory rheology was chosen to assess material behavior during flow. Viscosity variation as a function of temperature and chamber geometry was evaluated. Oscillatory mode tests were carried out to obtain information on product viscoelasticity. Tribological analysis was performed at different temperatures ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Casson model is a widely used model to describe the flow behavior of chocolate (Selvasekaran & Chidambaram, 2021). Principato et al, (2022) used Casson model to describe the flow behavior of commercial hazelnut/cocoa spread samples and obtained a good fit of the experimental data to the Casson model. Experimental shear rate and stress data obtained in this study were well‐fitted to the Casson model with the lowest R 2 value of 0.990.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Casson model is a widely used model to describe the flow behavior of chocolate (Selvasekaran & Chidambaram, 2021). Principato et al, (2022) used Casson model to describe the flow behavior of commercial hazelnut/cocoa spread samples and obtained a good fit of the experimental data to the Casson model. Experimental shear rate and stress data obtained in this study were well‐fitted to the Casson model with the lowest R 2 value of 0.990.…”
Section: Resultsmentioning
confidence: 99%
“…One reason of this slight decrease may be the reduction in the interaction of solid particles with decreasing levels of sugar in the complex system. Principato et al, (2022) investigated the rheological properties of five different commercial hazelnut‐based spreads and reported a reduction in the Casson plastic viscosity of samples with an increasing fat/sugar ratio. Moreover, it was thought that the sugar interacts with lecithin more than inulin, which may contribute to the retardation of the flow of the medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different commercial products were chosen to compare the newly developed product. The commercial products were chosen following previous research by the authors [ 21 ] according to the following features: the first one was identified as the top market player ( S B ), while the second one was targeted as a very high hazelnut content spread containing a 45% of hazelnut compared to the 13% of the market leader and many other cocoa/nut-based spreads on the market ( S C ). The macronutrient composition of our spread was evaluated and compared with the nutritional information of the selected market spreads.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers studied the rheological properties of different food products, such as mango juice (Zhou et al, 2017), apple juice (Salinas et al, 2019), kiwi fruit juice (Wang et al, 2020), hazelnut‐based spreads (Principato et al, 2021), fish gelatin (Cen et al, 2021), antioxidant‐rich tricolor pasta (Kaur et al, 2021), milk puddings (Li et al, 2021), to know the behavior of flow under different process conditions. The rheological properties, such as shear stress, storage modulus, and loss modulus, change with the temperature and concentration of the sample.…”
Section: Introductionmentioning
confidence: 99%